Relevansi Pendidikan Agama Islam Dengan Moderasi Beragama dan Radikalisme - Rama Armedi; Ilham Fawazi; Raihan Retriansyah Dilapanga; Harits Ibadurrahman; Namlul Wadi (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
The phenomenon of radicalism has become a significant issue in Indonesia, as it can disrupt the harmonious order of life in a diverse society. Radicalism not only occurs in the wider community but has also begun to penetrate the school environment. This study aims to analyze the relevance of Islamic Religious Education (PAI) to religious moderation and radicalism. This research is conducted through a literature review. This study will analyze related literature by identifying research gaps that need to be examined in Islamic education. The results show that Islamic Religious Education plays a crucial role in instilling values ​​based on religious moderation in the school environment. Islamic Religious Education also plays a significant role in preventing radicalism, namely by actualizing the Ministry of Religious Affairs' programs with the values ​​of religious moderation. This research contributes by providing a new perspective on the relevance of Islamic Religious Education to religious moderation and radicalism in Indonesia.